2013
DOI: 10.4155/fmc.13.127
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Pde Modulation in Treating Heart Disease

Abstract: Altered cyclic nucleotide-mediated signaling plays a critical role in the development of cardiovascular pathology. By degrading cAMP/cGMP, the action of cyclic nucleotide PDEs is essential for controlling cyclic nucleotide-mediated signaling intensity, duration, and specificity. Altered expression, localization and action of PDEs have all been implicated in causing changes in cyclic nucleotide signaling in cardiovascular disease. Accordingly, pharmacological inhibition of PDEs has gained interest as a treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 100 publications
(168 reference statements)
0
34
0
Order By: Relevance
“…Our analysis has revealed increased expression of genes implicated in heart disease including CLDN5, VWF, PDE6H, ITGA2B, and CA3 (80, 82, 83, 139, 140), as well as megakaryocyte differentiation (RGS18, GFI1B, and ARHGEF4 (75, 76)). ITGA2B is used as a biomarker for myocardial infarction risk and therapeutic modulation of phosphodiesterases is one strategy for treating cardiovascular disease.…”
Section: Discussionmentioning
confidence: 86%
“…Our analysis has revealed increased expression of genes implicated in heart disease including CLDN5, VWF, PDE6H, ITGA2B, and CA3 (80, 82, 83, 139, 140), as well as megakaryocyte differentiation (RGS18, GFI1B, and ARHGEF4 (75, 76)). ITGA2B is used as a biomarker for myocardial infarction risk and therapeutic modulation of phosphodiesterases is one strategy for treating cardiovascular disease.…”
Section: Discussionmentioning
confidence: 86%
“…Altered cyclic nucleotide-mediated signalling plays a critical role in the development of cardiovascular pathology, and is regulated by the action or inhibition of PDEs [79]. Altered expression of PDEs and cyclic nucleotide signalling have been implicated in a number of cardiovascular diseases, thus the pharmacological inhibition of PDEs has gained interest as an area for drug development for the treatment of HF.…”
Section: Other Small Molecule Therapies Showing Therapeutic Promise Fmentioning
confidence: 99%
“…However, a number of clinical trials have revealed chronic treatment with PDE3 inhibitors in heart failure patients is associated with increased mortality. Thus PDE3 inhibitors are now only used in patients with severe heart failure or those awaiting cardiac transplant (see review [79]). PDE5 expression is highly upregulated in the heart in response to pathological conditions and modulates cyclic GMP activity in the heart.…”
Section: Other Small Molecule Therapies Showing Therapeutic Promise Fmentioning
confidence: 99%
See 2 more Smart Citations